PROSES BERPIKIR SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI SPLTV DI SMA - Sirait, Natalia; Jamiah, Yulia; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractEach student has the ability to think different processes that are high-ability thinking process, thinking process of sedag and lower-minded thinking process. This research tries to describe the thinking process of high school students in solving the story problem on linear equation system of three variable (SPLTV) in SMA K Abdi Wacana Pontianak. By knowing the thinking process of students, it is expected to choose the appropriate teaching method for each student according to students' thinking ability and give attention to each student according to the thought process they have. This research is a qualitative descriptive research. The subjects of the study were XA SMA K Abdi Wacana Pontianak as many as 9 students: 3 high-ability students, 3 medium-skilled students and 3 lower-ability students. Methods of data collection conducted is by way of written tests and interviews. Based on the results of data analysis of writing tests and interviews obtained the results: 1.) The process of thinking three high-ability students in solving the story problem is already able to do the problem well and complete. 2.) The process of thinking three students are capable of solving the problem of the story is that there is still one student who has not been able to do the problem well and complete. 3.) Thinking process of three students capable down in solving the story problem that there are still two students who have not been able to do the problem well and Â Keywords: Thinking Process, SPLTV, High Capacity, Medium Capability, Underscore